Cardamonin protects nucleus pulposus cells against IL-1β-induced inflammation and catabolism via Nrf2/NF-κB axis. Issue 6 (5th March 2021) - Xie, Chenglong; Ma, Haiwei; Shi, Yifeng; Li, Junli; Wu, Hongqiang; Wang, Ben; Shao, Zhenxuan; Huang, Chongan; Chen, Jiaoxiang; Sun, Liaojun; Zhou, Yifei; Tian, Naifeng; et al.
Abstract : IL-1β promotes inflammatory response and extracellular matrix (ECM) degradation through NF-κB signaling pathway; while cardamonin attenuates the inflammatory response and ECM degradation by suppressing NF-κB signaling pathway via Nrf2/HO-1 axis. Abstract : Intervertebral disc degeneration (IVDD) is one of the major causes of low back pain, but effective therapies are still lacking because of its complicated pathology. It has been demonstrated that increased levels of interleukin-1β (IL-1β) may promote the development of IVDD. Cardamonin (CAR) is a chalcone extracted from Alpinia katsumadai and other plants. It exhibits an anti-inflammatory effect in multiple diseases. In the present study, we investigated the protective effects of CAR on rat nucleus pulposus (NP) cells under IL-1β stimulation in vitro and in a puncture-induced rat IVDD model in vivo . We explored the CAR treatment's inhibition of the expression of inflammatory factors such as cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), prostaglandin E2 (PGE2), nitric oxide (NO), tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) in rat NP cells. Moreover, the up-regulation of matrix metalloproteinase-13 (MMP-13) and thrombospondin motifs 5 (ADAMTS-5) and the degradation of aggrecan and collagen II induced by IL-1β were reversed by CAR. Mechanistically, we demonstrated that CAR inhibited nuclear factor kappa B (NF-κB) signaling by activating the nuclear factor erythroid-derived 2-like 2 (Nrf2) in IL-1β-induced rat NP cells. Furthermore, the protective effect of CAR was shown in the IVDD model through persistent intragastric administration. Taken together, our results revealed that CAR could activate the Nrf2/HO-1 signaling axis and be a novel agent for IVDD therapy.